„Walliser off Gultüre“. Die Wanderungsbewegung der Walser und Galtür - Jakob Franz Kathrein (Historia.scribere, 2016)
This bachelor thesis focusses on the history of the Walser migration in general and the settlement of Galtür in particular, looking at the reasons why the Walser people left their homeland and at the conditions under which they established new settlements. In addition this paper tries to find out whether traces of the Walser people and their culture still exist, particularly on the example of Galtür. Does a commemorative culture in the centres of the Walser migration and settlement exist in today’s Galtür? Do people there identify themselves as Walsers? The research to answer these questions is based on literature, online newspaper databases and empirical data gathered from an interview with an elderly resident of Galtür.